Measurement of the inclusive jet cross section in pp̄ collisions at s=1.96TeV - Abazov, V; Abbott, B; Abolins, M; Acharya, B; Adams, M; Adams, T; Aguilo, E; Ahn, S; Ahsan, M; Alexeev, G; Alkhazov, G; Alton, A; et al. (2008)
We report on a measurement of the inclusive jet cross section in pp̄ collisions at a center-of-mass energy s=1.96TeV using data collected by the D0 experiment at the Fermilab Tevatron Collider corresponding to an integrated luminosity of 0.70fb-1. The data cover jet transverse momenta from 50 to 600 GeV and jet rapidities in the range -2.4 to 2.4. Detailed studies of correlations between systematic uncertainties in transverse momentum and rapidity are presented, and the cross section measurements are found to be in good agreement with next-to-leading order QCD calculations. © 2008 The American Physical Society.